Some pottery assemblages in Samnite and Roman Pompeii in Insula VII, 4 - Ribera i Lacomba, Albert (Rei Cretariae Romanae Fautorum Acta, 2023)
We present groups of pottery from an insula near the forum. We can explain many histories through pottery assemblages. One of them is a part of a pit fill from the mid-2nd century BC. It does not appear to be domestic rubbish owing to the repetition of certain Italian cooking and tableware types indicating specific consumption. Furthermore, the repeated presence of a great number of horns, points to a ritual feast. At this moment, the surrounding space was empty of buildings, and it must have been dedicated to public and religious functions. This deposit is associated with the beginning of perfume production. Another ritual assemblage was related to the end of the perfume manufacture. This group filled a pool. A lagynos and many vessels were placed in the bottom at the end of the 2nd century BC.